1988
DOI: 10.1029/jb093ib11p13367
|View full text |Cite
|
Sign up to set email alerts
|

Large Earthquakes in the Tonga Region Associated With Subduction of the Louisville Ridge

Abstract: Subduction of the Louisville Ridge influences both interplate and intraplate seismicity in the southern Tonga region (22°S–26°S). Five earthquakes with diverse mechanisms and seismic moments greater than 1 × 1027 dyn cm have occurred in this region since 1975. These include two outer rise, one underthrusting, and two intermediate depth events, all of which occurred in close proximity to the subducting ridge. In order to understand better the nature of these events and to determine the role played by the Louisv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 43 publications
(21 reference statements)
2
35
0
Order By: Relevance
“…The Tonga trench is an exception to this class as the Mw=8.4, 17 November 1865 earthquake is the only known event of this subduction zone to have generated a far-field tsunami observable without instruments . This view of the Tonga subduction is coherent with the analysis of other seismologists (Christiensen and Lay, 1988;Lundgren and Okal, 1988), and of earthquake catalogues which indicate that the vast majority of large earthquakes (Mw≥7) nucleate at depths greater than 30 km. However, the great Indian Ocean tsunami of 26 December 2004 has demonstrated that two centuries of data are not enough to evaluate the maximum expected magnitude on a major thrust fault system.…”
Section: Tsunamis Source Potentialsupporting
confidence: 58%
“…The Tonga trench is an exception to this class as the Mw=8.4, 17 November 1865 earthquake is the only known event of this subduction zone to have generated a far-field tsunami observable without instruments . This view of the Tonga subduction is coherent with the analysis of other seismologists (Christiensen and Lay, 1988;Lundgren and Okal, 1988), and of earthquake catalogues which indicate that the vast majority of large earthquakes (Mw≥7) nucleate at depths greater than 30 km. However, the great Indian Ocean tsunami of 26 December 2004 has demonstrated that two centuries of data are not enough to evaluate the maximum expected magnitude on a major thrust fault system.…”
Section: Tsunamis Source Potentialsupporting
confidence: 58%
“…but large thrusting events seem relatively rare (Christensen and Lay, 1988), possibly favouring a model where interplate coupling is low (Lundgren and Okal, 1988). In addition, large tsunamis initiated in this source area have not been reported in the Marquesas archipelago.…”
Section: Simulation Of Tsunamis Initiated In the Tonga Trenchmentioning
confidence: 99%
“…The key parameter controlling the final amplification seems to be the fault strike angle that defines the oceanic domain where the maximum tsunami energy will be trapped and scattered. In order to separate the effect of the strike from the effect of the location, we have finally performed several tests for the southernmost 25 • S location, a place where the Louisville Ridge subducts and where the seismicity and active faulting pattern is rather complicated (Christensen and Lay, 1988). For this reason, the strike angle (180 • ) used in the first modeling may not be the value really involved in future earthquakes; thus, we used Figure 10 displays the amplifications obtained in the four Marquesas bays, compared to amplifications computed for the 16 • S source.…”
Section: Influence Of the Fault Strike Anglementioning
confidence: 99%
“…The association of the seismic gap with the ridge suggests that the stress state of the overriding plate has been altered by the subducting seamounts and their flexural moats (Bonnardot et al 2007). Three large earthquakes (M w = 7.4-7.5) located in close proximity to the subducting Louisville Ridge have been attributed to near-surface locking effects (Christensen & Lay 1988).…”
Section: G E O L O G I C a L S E T T I N Gmentioning
confidence: 99%